Relathionship of Organic Matter In Sediment and Macrozoobenthos Abundance in the Coastal Water of Belimbing Bay Batu Kalang, West Sumatera - Simamora, Ronaldy Saputra; Nedi, Syahril; Tanjung, Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in October 2015 in Batu Kalang, Belimbing  Gulf waters, South Coastal District, West Sumatera Province. Objective of this study was to determine the environmental condition of the waters of the Gulf of Belimbing, then to know the type and abundance of macrozoobenthos, then the relationship of sedimentary organic matter content with abundance of macrozoobenthos. The method used in this research is survey method. Analysis done quite well known water conditions through the value of diversity index (H') ranged from 3.31 to 3.47. Dominance index value (C) ranges from 0.11 to 012. Uniformity value (E) ranges from 0.71 to 0.77. Macrozoobenthos which is found as many as 27 species of gastropda grade and 2 species of bivalve class. Abundance obtained ranged 6,67- 10,00 ind / m2. The relationship between the sedimentary organic matter content with abundance of macrozoobenthos obtained regression equation y = 1.378 + 0,459x with a coefficient of determination (R2) of 0.128 and a correlation coefficient (r) of 0.358. Then the organic matter content of sediment have a weak relationship with the abundance of macrozoobenthos. Keywords: Organic Materials, macrozoobenthos, sediments, Gulf Belimbing